A comparative study into alterations of coenzyme Q redox status in ageing pigs, mice, and worms. (27th February 2014) - Onur, Simone; Niklowitz, Petra; Fischer, Alexandra; Metges, Cornelia C.; Grune, Tilman; Menke, Thomas; Rimbach, Gerald; Döring, Frank
Abstract Coenzyme Q derivatives (CoQ) are lipid soluble antioxidants that are synthesized endogenously in almost all species and function as an obligatory cofactor of the respiratory chain. There is evidence that CoQ status is altered by age in several species. Here we determined level and redox‐state of CoQ in different age groups of pigs, mice and Caenorhabditis elegans. Since these species are very different with respect to lifespan, reproduction and physiology, our approach could provide some general tendencies of CoQ status in ageing organisms. We found that CoQ level decreases with age in pigs and mice, whereas CoQ content increases in older worms. As observed in all three species, ubiquinone, the oxidized form of CoQ, increases with age. Additionally, we were able to show that supplementation of ubiquinol‐10, the reduced form of human CoQ10, slightly increases lifespan of post‐reproductive worms. In conclusion, the percentage of the oxidized form of CoQ increases with age indicating higher oxidative stress or rather a decreased anti‐oxidative capacity of aged animals. © 2014 BioFactors, 40(3):346–354, 2014